Hepatitis B virus perceptions and health seeking behaviors among pregnant women in Uganda: implications for prevention and policy - Joan Nankya-Mutyoba (BMC Health Services Research, 2019)
Abstract Background With most countries in sub-Saharan Africa (SSA) lagging behind schedule to implement a comprehensive viral hepatitis elimination strategy, several barriers to accurate information and hepatitis B virus (HBV) services still exist, that are unique to different regions. In an obstetric population of a high HBV burden SSA setting without antenatal HBV services, we systematically evaluated perceptions and prevention behavioral intentions in relation to HBV and liver cancer. Methods Eligible consenting pregnant women were recruited from public health care facilities in the central and northern regions of Uganda, between October 2016 and December 2017. Standardized procedures and instruments based on the health belief model and theory of planned behavior were used to collect data on socio-demographic characteristics, HBV perceptions and behavioral intentions. Descriptive analysis using Chi-square tests was done to obtain distribution of respondents by levels of perceived risk of HBV and liver cancer for themselves, their child under 5 years and their spouse. Modified Poisson regression analyses were used to evaluate relationships between perception variables and different behavioral outcomes (intention to screen, vaccinate and treat HBV). Results Perceived risk (PRR = 0.95(0.90–1.00), p = 0.055) was inversely associated with intention to screen for HBV. Conversely, perceived self-efficacy showed a consistent association with intention to screen for HBV (PRR = 1.18(1.10–1.23) p = 0.005), to vaccinate (PRR = 1.20(1.05–1.36) p = 0.006) and to seek treatment for HBV (PRR = 1.40(1.18–1.67) p < 0.001). Women from the north, compared to the central region (PRR = 1.76 (1.13–2.72) p = 0.012), and those who self-identified as Catholic (PRR = 1.85 (0.99–3.56) p = 0.056), and as Protestant, (PRR = 2.22 (1.22–4.04) p = 0.002), were more likely to have higher perceived self-efficacy, compared to Muslims. Age and education were not related to perceived self-efficacy. Conclusion Women in both regions hold incorrect perceptions of HBV and liver cancer risk, with women from the central reporting higher perceived risk than those from the north. High perceived self-efficacy influenced intention to participate in HBV prevention. Programs and policies geared towards enhancing HBV prevention in this sub-population may consider socio-cultural factors observed to influence prevention behaviors. These findings may guide HBV interventions aimed at improving capacity to seek HBV prevention services, thereby promoting HBV micro-elimination in this sub-population.